Household Nash equilibrium with voluntarily contributed public goods - Valérie Lechêne; Ian Preston (Institute for Fiscal Studies (IFS), 2005)
We study noncooperative models with two agents and several voluntarily contributed public goods. We focus on interior equilibria in which neither agent is bound by non negativity constraints, establishing the conditions for existence and uniqueness of the equilibrium. While adding-up and homogeneity hold, negativity and symmetry properties are generally violated. We derive the counterpart to the Slutsky matrix, and show that it can be decomposed into the sum of a symmetric and negative semidefinite matrix and another the rank of which never exceeds the number of public goods plus one. Under separability of the public goods the deviation from symmetry is at most rank two.
Keywords: D11; C72; 330; Nash equilibrium; Intra-household allocation; Slutsky symmetry; Nash-Gleichgewicht; Öffentliches Gut; Prinzipal-Agent-Theorie